Biological control and mechanism characterization of endophytic Bacillus velezensis SJ22 against bulb rot of Fritillaria taipaiensis P. Y. Li - Shijie Wang; Keke Chen; Mian Wei; Le Zhou; Jiaqi Guo; Jiaxiang Zhang; Langjun Cui; Yi Qiang (Biological Control)
Bulb rot in Fritillaria taipaiensis P. Y. Li, caused by Fusarium spp., is a destructive soil-borne disease that severely affects the yield and quality of F. taipaiensis. Chemical fungicides are currently the primary means of controlling this disease; however, their use poses risks to human health and the environment. Biological control is thus a preferable alternative to counteract the threats associated with pathogens. In this study, an endophytic bacterium, designated SJ22, was isolated from bulb tissue of F. taipaiensis, and it exhibited significant antagonism against Fusarium spp., with inhibition rates on plates ranging from 84.35% to 89.96% and a control rate of 73.38% in pot experiments. Morphological observations and phylogenetic analyses identified the isolate SJ22 as Bacillus velezensis. Furthermore, the antifungal mechanisms of SJ22 include the inhibition of spore germination, alteration of hyphal morphology, and disruption of cell membrane integrity. Its volatile organic compounds exhibited broad-spectrum antifungal activity in vitro, with an inhibition rate of 28.36% to 59.12%, and demonstrated significant control efficacy in vivo. Transcriptome analysis revealed that SJ22 induced systemic resistance in F. taipaiensis by upregulating defense-related genes, primarily through enhancing the phenylpropanoid biosynthesis pathway and promoting the salicylic acid/ethylene signaling pathway to induce the production of pathogenesis-related proteins and increase the activity of defense-related enzymes. In summary, we isolated an endophytic bacterium that exerts its biocontrol function through both inhibiting pathogen growth and inducing resistance.